Penerapan Metode Balanced Scorecard Sebagai Tolak Ukur Pengukuran Kinerja CV. Sumber Pinus Jaya - Levina Cahyaning Eka Candra; Ujang Syahrul Mubarok; Kukuh Harianto (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to determine and analyze the application of the balanced scorecard method as a benchmark for performance measurement at CV. Sumber Pinus Jaya. The research method used is a qualitative method, because this study does not aim to prove a hypothesis but rather aims to reveal facts and circumstances that occur at the time of the study. From the results of the discussion, it shows that the balanced scorecard method translates performance measures that have four indicators, namely in the financial perspective shows fluctuating numbers, the customer perspective shows good results, the internal business process perspective shows that the company has carried out an innovation process such as the concept of making furniture following current developments, the growth and learning perspective shows good company performance conditions because it can improve the quality of its employees. From the discussion above, it can be concluded that the use of the balanced scorecard method can be used as a benchmark for the success of a company. In order to be applied properly to the company, improvement efforts are needed both internally and externally.